100m freestyle: factors affecting performance - Aspenes, S. T.; Kjendlie, P. L. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: 100m freestyle has been subject to rapid development for the last few years. Although much focus has been directed towards the swimming suit, it remains an eligible wish that the performance within it have also evolved. Few studies have established statistical models designed to predict swimming-performance, partly as powerful multivariable analyses demand high numbers of participants. Unable to accommodate to those demands, this study aimed at investigating performance determining factors in 100m freestyle. METHODS: Data were from 13 female and 11 male Norwegian national-level swimmers, aged 15 to 24. Sprint velocities, time trials, oxygen uptake and in-water force measurements were measured according to Aspenes et al. (2009). After controlling for normality, distribution was calculated as mean±standard deviation and linear regressions as standardized and p-value with 100m performance as the dependent variable. RESULTS: Mean 100m time was 65.5±3.7 seconds in females and 58.7±2.1 seconds in males. In females, maximal 50m freestyle performance ( =0.96, p<0.001), maximal velocity in 25m sprint ( =-0.93, p<0.001), maximal 400m freestyle performance ( =0.83, p<0.001), maximal swimming force ( =-0.82, p=0.001), velocity at VO2peak ( =-0.71, p<0.01) and VO2peak ( =-0.55, p=0.05) was associated with 100m performance in order of significance. In males, maximal 50m ( =0.96, p<0.001) and 400m ( =0.83, p<0.001) freestyle performance, maximal swimming force ( =-0.82, p<0.01), maximal velocity in 25m sprint ( =-0.74, p<0.01), supine reaching height ( =-0.70, p<0.05), weight ( =-0.66, p<0.05) and height ( =-0.63, p<0.05) were associated with 100m performance. Factors that did not associate with 100m performance in either gender were age, maximal land strength, swimming economy, and stroke length and -rate during maximal swimming. DISCUSSION: Our analyses showed that the strongest associates of 100m swimming performance were performance in other swimming events, and surprisingly, 400m freestyle was the second strongest associate. Other studies have shown that performance to a high degree relies on favourable anthropometric features, but in our small sample this was only valid for males. In contrast to established knowledge, we did not find any association between stroke length or - rate and performance in any gender. Aspenes, ST, Kjendlie, PL, Hoff, J, Helgerud, J. Combined strength and endurance training in competitive swimmers, JSSM, 8:357-365. 2009.